The well-tempered color circle: A chromatic Gestalt - Jan J. Koenderink; Andrea J. van Doorn; Doris I. Braun (i-Perception)
The “Color Circle” is an important chromatic Gestalt in the visual arts. There is not really a formal equivalent in conventional colorimetry. The fact that the hues can be linearly ordered and that such an order is necessarily periodic was intuited by artists in the early 19th century, but only formally explained by Ostwald and later Schrödinger a century later. As with musical keys, various metrical orders are in common use. Is there such a thing as a “well tempered” order? We consider this an issue for experimental phenomenology. We discuss an attempt based on observations by 30 (nonartist) observers.